Comparative DNA profiling, botanical identification and biological evaluation of Gazania longiscapa DC and Gazania rigens L. - Wafaa M. El Kady; Abeer A.A. Salama; Samar Y. Desoukey; Eman G. Hagag; Siham M. El-Shenawy; M.A. El-Shanawany (Faculty of Pharmacy, Cairo University, 2015)
Gazania longiscapa DC and Gazania rigens L. are species of cultivated ornamental plant that grow in Egypt. Genus Gazania has a role in folk medicine to prevent toothache; this study presents a comparative investigation of genetic and botanical features of root, rhizome, leaves and flowers of the two Gazania species and comparing their biological activity as analgesic and antiinflammatory as related to their folk medicinal use. The genetic and botanical differences between the two Gazania species are reported for the first time in this study. The results contribute toward validation of the traditional use of Gazania showing that both species are safe for oral administration and they exhibit significant antinociceptive and anti-inflammatory effects in a dose dependent manner.